2017
DOI: 10.1051/parasite/2017042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the insecticidal activity of afoxolaner against Aedes aegypti in dogs treated with NexGard®

Abstract: Twelve healthy dogs were studied in this parallel group, blinded, randomised, and negative controlled efficacy study. On Day -1, the 12 dogs included were ranked within sex in descending order of individual pre-treatment (Day -5) fed mosquito counts and randomly allocated by blocks of two dogs to the untreated control group or the afoxolaner-treated group. NexGard® (Merial, now part of Boehringer Ingelheim Animal Health) was administered orally on Day 0 in accordance with the European label instructions. On Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…There are limited data on the infestation of dogs and cats by C. lectularius bedbugs. They are thought to bite pets, but the frequency remains unknown [ 1 , 17 ]. The fact that bedbugs are maintained in the laboratory using weekly feeding on rabbits provides initial evidence that mammals other than humans may be functional hosts [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on the infestation of dogs and cats by C. lectularius bedbugs. They are thought to bite pets, but the frequency remains unknown [ 1 , 17 ]. The fact that bedbugs are maintained in the laboratory using weekly feeding on rabbits provides initial evidence that mammals other than humans may be functional hosts [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoptes scabiei , Demodex canis , Otodectes cynotis ) [ 2 , 3 , 5 ], and has demonstrated insecticidal activity against hematophagous flying insects (i.e. sandflies, Phlebotomus perniciosus , and mosquitoes, Aedes aegypti ) through the treatment of dogs [ 17 , 21 ]. Recently, an insecticidal effect of afoxolaner and fluralaner has also been demonstrated in treated dogs against kissing bugs ( Triatoma infestans ), the vector of Chagas disease [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of each 1-h exposure period, sandflies were smoothly vacuumed from the enclosure, categorized (male/female), counted and assessed for viability status (live/dead). As classically performed for insects and acarians, moribund sandflies were counted as live, which is more restrictive in the assessment of effectiveness [22]. Sandflies were also categorized as either fed or unfed, separated, and transferred to containers.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the insecticidal activity of afoxolaner against Aedes aegypti mosquitoes at 24 h postexposure was demonstrated. It showed that A. aegypti mosquitoes ingested a lethal dose of afoxolaner during their blood meal [22]. Based on these results, we hypothesized that afoxolaner could also kill sandflies that feed on afoxolaner treated dogs [13].…”
Section: Introductionmentioning
confidence: 95%
“…Mosquitoes readily fed on the dogs indicating that the treatment was not repellent. At 24 h after feeding, 98 and 75.3% of the female mosquitoes were killed when exposed to dogs on day 2 and 29 after the dogs were dosed, respectively [ 94 ].…”
Section: Chemical Treatmentsmentioning
confidence: 99%